2017
DOI: 10.4102/sajip.v43i0.1458
|View full text |Cite
|
Sign up to set email alerts
|

Leader–member exchange fosters work engagement: The mediating role of job crafting

Abstract: Orientation: The right balance between job demands and job resources are essential for employees to bring energy and enthusiasm to work. Employees who experience high-quality relationships with their supervisors may actively craft their job demands and job resources and feel more engaged.Research purpose: The current study examined the associations between leader–member exchange (LMX), job crafting and work engagement. Motivation: This study attempts to gain more insight in the associations between LMX, job cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 81 publications
3
48
0
6
Order By: Relevance
“…Future studies should delve more into the quality of employee‐supervisor relationships, or leader‐member exchanges, that are characterized by a high degree of mutual trust, respect, and obligation. Leaders who provide a high level of job resources for their followers, especially in the form of autonomy, social support, and positive feedback (Breevaart, Bakker, Demerou, & van den Heuvel, 2015; Radstaak & Hennes, 2017), may motivate employees to proactively search for or shape various experiences to find their calling.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should delve more into the quality of employee‐supervisor relationships, or leader‐member exchanges, that are characterized by a high degree of mutual trust, respect, and obligation. Leaders who provide a high level of job resources for their followers, especially in the form of autonomy, social support, and positive feedback (Breevaart, Bakker, Demerou, & van den Heuvel, 2015; Radstaak & Hennes, 2017), may motivate employees to proactively search for or shape various experiences to find their calling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high commitment human resource management, which includes practices such as extensive training, empowerment, and participation in decision-making, has been indicated to positively related to approach crafting (Meijerink, Bos-Nehles, & de Leede, 2018). Similarly, empirical and meta-analytic studies have found a positive relationship between approach crafting and good work design, which includes features such as job autonomy (Kim, Im, & Qu, 2018;Rudolph et al, 2017), job enlargement (Berdicchia, Nicolli, & Masino, 2016), opportunity for professional development (Nipper, van Wingerden, & Poell, 2018), task identity, task significance (Kim & Lee, 2016), feedback, social support, leadermember exchange (Berdicchia & Masino, 2017;Gordon, Demerouti, Le Blanc, & Bipp, 2015;Radstaak & Hennes, 2017), and skill utilization (Cullinane, Bosak, Flood, & Demerouti, 2017). In addition, Cullinane et al (2017) indicated that the positive relationship between daily skill utilization and approach resources crafting was stronger when employees had high boundary control and low task interdependence in their general roles.…”
Section: Antecedents Of Approach Craftingmentioning
confidence: 99%
“…In this category, researchers have also applied a behavioral modeling framework (Bandura, 1986) to theorize and show that job crafting behaviors can be imitated by coworkers (e.g., Bakker et al, 2016;Demerouti & Peeters, 2018). Finally, researchers have investigated the role of leadership as an antecedent of job crafting, including servant leadership (Bavik et al, 2017;Harju et al, 2018), employee-oriented leadership (Lichtenthaler & Fischbach, 2018b), transformational leadership (Hetland et al, 2018), and the quality of the leader-member exchange relationship (Radstaak & Hennes, 2017). These studies mostly show a positive relationship between a supportive leadership style and approach forms of job crafting, but they provide limited evidence that leadership style affects avoidance crafting.…”
Section: Social Context As Influencing Individual Job Craftingmentioning
confidence: 99%